Enterprise digital transformation and customer concentration: An examination based on dynamic capability theory - Liu, Laihui; An, Suxia; Liu, Xiangyu (Frontiers in Psychology, 2022)
Digital transformation of traditional enterprises can better develop new customer relationships and help mitigate the business risk of their over-reliance on single-customer relationships. This paper obtains data on the frequency of the word "digital transformation" in the annual reports of listed companies between 2011 and 2019 by using Python, theoretically sorts out the inner mechanism of digital transformation to reduce customer concentration, and examines the impact of digital transformation on customer concentration. This paper finds that digital transformation significantly reduces customer concentration and has driven the innovation of business model in the digital economy, and this finding remains robust after using PSM and instrumental variables to address the endogeneity issue. Digital transformation reduces firms' dependence on major customers through three mechanisms: increasing firms' innovation capabilities, reducing firms' operating costs, and enhancing customer satisfaction. Compared with state-owned enterprises, the impact of digital transformation on reducing the dependence of non-state enterprises on major customers is greater; the implementation of digital transformation strategies is more helpful in reducing customer concentration for enterprises engaging in active interactions with customers; the digital transformation of companies in regions with a higher level of digital development has had a greater effect on reducing customer concentration than in regions with a lower level of digital development. The economic consequence test finds that digital transformation diversifies customer structure and reduces business risks. The findings of this paper provide important policy insights for exploring the impact of digital transformation on customer concentration.